Betatron Cooling of Electrons in Martian Magnetotail. Issue 13 (5th July 2021) - Guo, Z. Z.; Fu, H. S.; Cao, J. B.; Fan, K.; Yao, Z. H.; Liu, Y. Y.; Chen, Z. Z.; Wang, Z.; Liu, X. Y.; Xu, Y.; Mazelle, C.; Mitchell, D. L.
Abstract: Betatron cooling, a plasma process losing particle energy in the perpendicular direction but reserving particle energy in the field‐aligned direction, is a consequence of magnetic depression under the conservation of magnetic moment. Such process has been widely studied in the Earth's magnetosphere but has never been reported in other planetary environment. Here, by utilizing the Mars Atmosphere and Volatile EvolutioN (MAVEN) measurements, we report two events of betatron cooling in the Martian magnetotail. In one of the events, betatron cooling occurs in the suprathermal and energetic ranges of electrons, whereas in the other event, it occurs in the thermal‐energy range. We quantitatively reproduce these two processes by using an analytical model. Gratifyingly, the cooling factor derived from the analytical model agrees well with the observation of magnetic depression. These results, for the first time demonstrating the betatron‐cooling effect beyond the Earth, are useful to understand the electron dynamics in the planetary magnetosphere. Plain Language Summary: Under conservation of the magnetic moment, electrons can lose energy in the perpendicular direction but reserve energy in the field‐aligned direction when magnetic field strength becomes weaker. Such process, called betatron cooling, has not been reported in the extraterrestrial planetary environment. Using the Mars Atmosphere and Volatile EvolutioN (MAVEN) data and an analytical model, for the first time, we quantitatively demonstrate and reproduce this cooling process of electrons in the Martian magnetotail, and the cooling factor derived from the analytical model agrees well with the observation. Our study promotes the understanding of the electron dynamics in the planetary magnetosphere. Key Points: We provide the first evidence of electron betatron cooling in Martian magnetotail We quantitatively reproduce this cooling process by using an analytical model The cooling factor derived from the model agrees very well with the observation